Lean Combustion technology and control - Dunn-Rankin, Derek (Academic Press, 2008)
Combustion under sufficiently fuel-lean conditions can have the desirable attributes of high efficiency and low emissions, this being particularly important in light of recent and rapid increases in the cost of fossil fuels and concerns over the links between combustion and global climate change. Lean Combustion is an eminently authoritative, reference work on the latest advances in lean combustion technology and systems. It will offer engineers working on combustion equipment and systems both the fundamentals and the latest developments in more efficient fuel usage and in much-sought-after reductions of undesirable emissions, while still achieving desired power output and performance. This volume brings together research and design of lean combustion systems across the technology spectrum in order to explore the state-of-the-art in lean combustion and its role in meeting current and future demands on combustion systems. Readers will learn about advances in the understanding of ultra lean fuel mixtures and how new types of burners and approaches to managing heat flow can reduce problems often found with lean combustion such as slow, difficult ignition and frequent flame extinction. The book will also offer abundant references and examples of recent real-world applications. Covers all major recent developments in lean combustion science and technology, with new applications in both traditional combustion schemes as well as such novel uses as highly preheated and hydrogen-fueled systems Offers techniques for overcoming difficult ignition problems and flame extinction with lean fuel mixtures Covers new developments in lean combustion using high levels of pre-heat and heat re-circulating burners, as well as the active control of lean combustion instabilities.